2005
DOI: 10.3390/ijerph2005030009
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Kinetics of Escherichia coli and Salmonella sp on Two Soil Layers Associated with a Groundwater Table in Yaounde, Cameroon (Central Africa)

Abstract: Abstract:A laboratory study has been carried out on two soil layers (H X and H Y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
(52 reference statements)
1
6
0
1
Order By: Relevance
“…Bacterial retention on soil particles during water infiltration through soil column is sometimes selective (Nola et al . , ). It has been indicated that the inactivation rate of E. coli pathogenic strains in sand‐free groundwater was approximately 0.03 log unit per day, and 0.04 and 0.2 log unit per day for Salmonella typhimurium and Staphylococcus aureus , respectively (John & Rose ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial retention on soil particles during water infiltration through soil column is sometimes selective (Nola et al . , ). It has been indicated that the inactivation rate of E. coli pathogenic strains in sand‐free groundwater was approximately 0.03 log unit per day, and 0.04 and 0.2 log unit per day for Salmonella typhimurium and Staphylococcus aureus , respectively (John & Rose ).…”
Section: Resultsmentioning
confidence: 99%
“…This could be due the variation of its retention potential or its inactivation on the soil layer particles during the infiltration or percolation of contaminated water. Bacterial retention on soil particles during water infiltration through soil column is sometimes selective (Nola et al 2005(Nola et al , 2006. It has been indicated that the inactivation rate of E. coli pathogenic strains in sand-free groundwater was approximately 0.03 log unit per day, and 0.04 and 0.2 log unit per day for Salmonella typhimurium and Staphylococcus aureus, respectively (John & Rose 2005).…”
Section: Nola Et Almentioning
confidence: 99%
“…Nola et al (2005) found a rapid attachment within 30 min for both E. coli and Salmonella spp. This may be explained by attachment.…”
Section: Discussionmentioning
confidence: 92%
“…This may be explained by attachment. Nola et al (2005) found a rapid attachment within 30 min for both E. coli and Salmonella spp. For Salmonella spp., a high proportion of cells attached to the soil particles with a K f of 506 and 847 in two soil types.…”
Section: Discussionmentioning
confidence: 92%
“…Cette minéralisation est liée aux ions contenus dans les eaux analysées ainsi qu'à la nature équatoriale du sol de la zone de Yaoundé (NOLA et al, 2006). En effet, RODIER (1996) La caractérisation morphologique de C. cayetanensis au microscope montre que les oocystes sont arrondis, mesurent de 8 à 10 µm de diamètre et se présentent sous deux formes (sporulées et non sporulées).…”
Section: Discussionunclassified